Adhesion mechanism of a gecko-inspired oblique structure with an adhesive tip for asymmetric detachment. (22nd October 2015) - Sekiguchi, Yu; Takahashi, Kunio; Sato, Chiaki
Abstract: An adhesion model of an oblique structure with an adhesive tip is proposed by considering a limiting stress for adhesion to describe the detachment mechanism of gecko foot hairs. When a force is applied to the root of the oblique structure, normal and shear stresses are generated at contact and the adhesive tip is detached from the surface when reaching the limiting stress. An adhesion criterion that considers both the normal and shear stresses is introduced, and the asymmetric detachment of the oblique structure is theoretically investigated. In addition, oblique beam array structures are manufactured, and an inclination effect of the structure on the asymmetric detachment is experimentally verified.